The Routledge handbook of accounting information systems - Quinn, Martin, 1973-; Strauss, Erik, 1982- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"The Routledge Handbook of Accounting Information Systems is a prestige reference work offering a comprehensive overview of the state of current knowledge and emerging scholarship in the discipline of AIS. The pace of technological driven change is rapid, and this revised edition provides a deeper focus on the technical underpinnings and organisational consequences of accounting information systems. It has been updated to capture the changes in technology since the previous edition. It now includes chapters and scholarly thought on artificial intelligence, predictive analytics and data visualisation, among others. Contributions from an international cast of authors provide a balanced overview of established and developing themes, identifying issues and discussing relevant debates. The chapters are analytical and engaging. Many chapters include cases or examples, and some provide additional resources for readers. The chapters also provide a reflection on where the research agenda is likely to advance in the future. This is a complete and indispensable guide for students and researchers in accounting and accounting information systems, academics and students seeking convenient access to an unfamiliar area, as well as established researchers seeking a single repository on the current debates and literature in the field"--
Earlier edition published as: The Routledge companion to accounting information systems.
OCLC-licensed vendor bibliographic record.
Keywords: Accounting -- Data processing; Management information systems; BUSINESS & ECONOMICS / Accounting / General; BUSINESS & ECONOMICS / Accounting / Financial; BUSINESS & ECONOMICS / Auditing